Education, Prevention and Mother-Child Promotion in Oral Health: Experience Report in an University Hospital in Brazilian Southeast - Vargas de Jesus Alves, Thamyres; Sarcinelli Barbosa, Roberto; Pfister Sarcinelli Almilhatti, Alice; Tonini Dos Santos Pacheco, Karina; Dutra Degli Esposti, Carolina; Baroni de Carvalho, Raquel (Guará Journal, 2019)
The article reports the lived experience in an extension project. This project was focused in mother and children’s oral health for pregnant women, puerperal, children and babies, which were hospitalised in University Hospital Cassiano Antônio Moraes (HUCAM) in Vitoria, ES, Brazil. The project is developed by teachers and academics of the dentistry course from Universidade Federal do Espírito Santo (Ufes), since 2010. The project started with a bibliographic survey about coletive oral health and subsequent monthly group discussion, building the theoretical foundations for planning and development of the activities. The colective accomodations of the maternity and children ambulatory were visited weekly, under the teacher’s supervision. Orientations about oral hygiene for mothers, newborn and children were given by the students. They also answered to people’s questions weekly or everytime that a visit occured. They also were there to give informations about the dentristry services offered by the hospital and the university. Around 1455 people were supported by the project between 2010 and 2018. Although some mothers had a lack of interest in the beginning to receive the information, many were very receptive during the meeting. The project proved to be important for the promotion of oral health of these pregnant women, postpartum women, infants and children, by the early insertion of oral health care, mainly by the mothers’ direct orientation by our dentistry students.